Determinants of Bank Group Profitability in the Philippines from 2008 to 2019: A Panel Data Regression Approach - Pamatmat, Raniel Jude A. (Philippine Management Review, 2023)
The goal of this study is to determine the internal and external factors that influence the profitability of the Philippine banking sector. This study applies a fixed effects panel regression model to aggregated quarterly data of the commercial, universal, rural, thrift, and cooperative bank groups in the Philippines from 2008 to 2019. Return on Asset (ROA) and Return on Equity (ROE) values are used as dependent variables in two different models. The estimation shows that of the internal factors tested, bank group size (-), credit risk (-), income diversification (+), capitalization (+), and interest spread (+) are significant determinants of both ROA and ROE. Of the external factors, foreign exchange rates (+) and interest rates (-) are found to be significantly related to profitability. These results serve as a valuable reference for further study of the performance of the Philippine banking sector.